Challenges of higher education - Abd Razak, Dzulkifli (2009)
THE 2009 Global Higher Education Forum jointly organised by the Higher Education Ministry and Universiti Sains Malaysia (USM) last week took off with a bang marked by the keynote and opening speech by Minister Datuk Seri Mohamed Khaled Nordin. The speech created tremendous impact on the conference themed Recent Trends, Future Directions, which covers issues of regionalism and harmonisation, the influence of the economic crisis, as well as future relevance and scenarios of higher education. In his speech, Mohamed Khaled elaborated on five important topics challenges in transforming higher education; issues which have impacted it; the nature of authority in tertiary institutions; cooperation versus competition and commercialisation of research.